A cross-sectional and longitudinal structural magnetic resonance imaging study of the post-central gyrus in first-episode schizophrenia patients. Issue 1 (30th January 2015) - Ferro, Adele; Roiz-Santiáñez, Roberto; Ortíz-García de la Foz, Victor; Tordesillas-Gutiérrez, Diana; Ayesa-Arriola, Rosa; de La Fuente-González, Noemi; Fañanás, Lourdes; Brambilla, Paolo; Crespo-Facorro, Benedicto
Abstract: The post-central gyrus (PoCG) has received little attention in brain imaging literature. However, some magnetic resonance imaging (MRI) studies have detected the presence of PoCG abnormalities in patients with schizophrenia. Fifty-six first-episode schizophrenia patients, selected through the program of first-episode psychosis (PAFIP) and carefully assessed for dimensional psychopathology and cognitive functioning, and 56 matched healthy controls were scanned twice over 1-year follow-up. PoCG gray matter volumes were measured at both time-points and compared between the groups. Differences in volume change over time and the relationship between PoCG volume and clinical and cognitive variables were also investigated. The right PoCG volume was significantly smaller in patients than in controls at the 1-year follow-up; furthermore, it was significantly smaller in male patients compared with male controls, with no differences in female. Although there was no significant time by group interaction in the overall sample, a trend-level interaction was found for the right PoCG in males. This is the first study, as per our knowledge, to focus on PoCG in first-episode schizophrenia patients. The presence of PoCG abnormalities in the first year of schizophrenia suggests a possible contribution to the pathophysiology of the illness, probably as part of a more extensive network of abnormalities.